How to scale up innovations to achieve transformative impact - Amarnath, Giriraj; Smith, Mark (CGIAR System Organization, 2022)
ClimBeR Governance 4 Resilience (Work Package 4) developed a framework to scale innovations for transformative impact. The framework has four elements: 1) Changing the narrative, 2) Deepening the analysis, 3) Strengthening the alliances, 4) The process of change: applying lessons learned. This framework is being applied to ClimBeR research on governance in Kenya, Morocco, Senegal, Guatemala and the Philippines.